Risk Mitigation of Raw Material Warehouse Activity Processes Cooking Oil Packaging PT. Sinarmas, Tbk - Nugroho, Nurwidiah Sulistyo (Universitas Syiah Kuala, 2023)
PT. Sinarmas, Tbk is a Cooking Oil producer which has several Cooking Oil product lines. In downstream business, our processing facilities are capable of producing high quality Cooking Oil products for supplying international and national markets throughout Indonesia. High consumption of cooking oil encouraging the Cooking Oil industry to encourage production. To fulfill this, then required Genre chain supply Which Good Especially from side Warehousing Packaging Oil Fry. Study This aims to determine the risks that exist in PT's packaging raw material warehouse activities. Sinarmas, Tbk Plant Surabaya And designing strategy mitigation risk on activity warehouse material standard packaging PT. Sinarmas, Tbk. The next stage is to map warehouse activities using the Supply Chain Operation model Reference (SCOR) to find out which activities are included in the core processes in the SCOR model. After That done identification risk And evaluation based on Method HORROR ( House Of Risk ) Results evaluation HOR is a priority in preparing mitigation strategies for PT Sinarmas, Tbk. Based on research results It is concluded that there is 1 Risk Agent in the red area which indicates the risk level critical occurs at Risk agent A5, namely There is no updating of data regarding raw materials that have been used Occurs in the Plan Process with the highest risk value of 35, so priority treatment is required mitigation. And there is 5 Risk agent that is A1, A13, A20 Which is Risk agent Lack of facility supporter For demolish load own mark risk smallest as big as 8,A25,A29 Which is at in area Yellow Which own medium risk level where risk management needs to be carried out routinely and this must be implemented Occurs in the Plan, Source, Delivery and Return processes, and occurs at low risk levels on Process Source on Risk Agent A1 That is Information About Delivery Schedule. Change from condition risk Which obtained need designed strategy mitigation so that No happen disturbance on system inventory in the warehouse in PT. Sinarmas.